(untitled) (Boca Raton, 2009)
An organized exploration of new developments in academic and current food industry practices, Engineering Aspects of Thermal Food Processing presents groundbreaking advances in the physical and engineering aspects of thermal food processing, paying particular attention to modeling, simulation, optimization, online control, and automation
Keywords: Thực phẩm,Food,Food industry and trade; Tác dụng của nhiệt,Effect of heat on